New approaches in evaluating metallic candidates for bioabsorbable stents. Issue 5 (October 2012) - Bowen, Patrick K.; Drelich, Jaroslaw; Buxbaum, Robert E.; Rajachar, Rupak M.; Goldman, Jeremy
Abstract : A series of unconventional approaches has been developed at Michigan Technological University, which is able to screen candidate materials for use in bioabsorbable (or bioresorbable) stents by reducing the scale of necessary animal studies and the complexity of biocorrosion analyses. Using a novel in vivo approach, materials formed into a simplified wire geometry were implanted into the wall of the abdominal aorta of rodents for several weeks or months to measure the extent of in vivo degradation, quantify mechanical strength over time, characterize the resulting products, and assess biocompatibility. An in vitro method was developed to identify bioabsorbable candidate materials, reproduce the corrosion products formed in vivo, and predict the degradation rate of stent materials. To accomplish this goal, wires were encapsulated in an extracellular matrix and corroded in cell culture media in vitro. Encapsulation of the wires in vitro was necessary in order to mimic in vivo stent encapsulation within a neo-intima. Alternatively, accelerated in vitro corrosion for materials with very low corrosion rates was accomplished by exposing fibrin-coated wires to a steady flow of cell culture media. After in vivo and in vitro tests, wires were subjected to tensile testing to quantify the rate of material degradation and loss of mechanical strength.